Pengolahan Moke Arak Berbahan Dasar Air Lontar Secara Tradisional di Kecamatan Aimere Kabupaten Ngada - Bao, Antonia Paulina; Limbu, Umbu N.; Meo, Monika Moi (Jurnal Pendidikan Ilmu Pengetahuan Alam (JP-IPA), 2025)
White moke, arak moke, red moke, tuak, and wine are the traditional alcoholic beverages of Ngada Regency. The Aimere region is home of the factories that create Moke Arak, the most popular beverage in this regency. The base ingredient for the moke prepared in Aimere district is lontar sap, as opposed to the coconut sap used in Bajawa district. This lontar sap is processed to create moke arak. Some of the factories still employ conventional techniques. One of the community's sources of income is the traditional processing of moke arak, which has been carried down from our ancestors' time to the present. The study goal is to comprehend the traditional method of creating moke arak using lontar sap and the variables that affect it. This study used a descriptive exploratory approach, gathering data using three methods: documentation, interviews, and observation. Qualitative descriptive analysis was used to examine the data. According to the study's findings, Aimere's moke arak is processed by sap gathering, fermentation, distillation, and drying. The basic material of palm sap, fermentation time, ingredient composition, temperature during fermentation and destillation, size of the distillation bamboo, and drying time are all factors that impact the manufacture of moke arak.